Berau coal in East Kalimantan; Its petrographics characteristics and depositional environment - Nana Suwarna; Bambang Hermanto (Indonesian Journal on Geoscience, 2007)
http://dx.doi.org/10.17014/ijog.vol2no4.20071To asses the characteristics of the Early to Middle Miocene Berau coal in the Berau Basin, leading to interpretation of coal depositional environments, some fresh outcrop and subcrop samples and also drill cores of the coals have been analyzed microscopically. Coal petrographic analysis was performed on twenty four coal samples from the Middle Miocene Lati Formation. Vitrinite, present in a high value, and ranging between 66.2 - 96.2%, is dominated by vitrinite B. On the other hand, inertinite and exinite, showing a similar value, exist in a low to moderate amount. Vitrinite reflectance, present in a low value, varies from 0.40 - 0.58%. Low mineral matter content is dominated by clay minerals (0.4 - 6.6%) with minor pyrite. Transitions from wet and very wet forested swamps to drier conditions with lower tree density are indicated by the higher content of vitrinite B, whilst a reverse trend is indicated by the lower content of vitrinite A. Petrographic indices obtained from facies diagnostic macerals show that an accumulation of the ancient peats under prevailing relatively wet limited influx clastic marsh to very wet forest swamps or moors is considered. The composition of the coal samples supports the interpretation of a system of fluvial to meandering streams in an upper delta plain environment. The original peat-forming vegetation was composed mainly of cellulose rich, shrub-like plants, tree ferns, herbaceous plant communities, with minor amount of trees. Thereby, the organic facies concept is thus applicable in basin studies context and has potential to become an additional tool for depositional environment interpretation.